Hygiene habits and carriers in families with a child who has had typhoid fever - Alvarez,M. de la Luz (1992)
The relationship between asymptomatic shedding of bacterial enteropathogens and the hygiene habits of families who have had a child with typhoid fever (TF) are investigated. The sample was made up of 80 families: 40 families in which one child had had TF (Group A) and 40 in which no children or either of the parents had had a history of TF (Group B). In each group 20 families belonged to a low socieconomic status (SES) and 20 to a high SES. A structured interview was used to evaluate the SES and the hygiene habits of the child; observations were made to measure the hygiene habits of the family (toilet, kitchen and food preparation) and bacteriological studies (fecal samples and hand markers). Results show that carriers were more frequent in Group A than in Group B. The bacterial species found were significantly more numerous in Group A than in Group B (fecal samples: E. coli, the classic serotypes, Shigella ssp, and hand markers: E. coli). Families of Group A had higher carriage rates than those of Group B. Finally there exists a significantly higher association between inadequate hygiene habits and carrier families. These results show the need to teach specific habits of proper hygiene to the entire population, because the fact of belonging to the high SES does not in itself preclude inadequate hygiene habits.